Sustainable tourism development in mountain regions. The case study of the Jabel Mesaad, Algeria - Khalfallah, Boudjemaa (Technium Social Sciences Journal, 2023)
The natural environment is one of the most important resources for tourism development. Recently, a new type of tourism has emerged, especially based on nature. A group has emerged in Algeria and elsewhere who prefer to spend their holidays in order to escape the noise and crowds of the city and enjoy the beauty and purity of nature and the diversity of the aesthetics of its landscapes. You can also take advantage of everything related to the specificity of the place and local cultures. Algeria is one of the countries that seeks to achieve this trend. It has great mountain tourism potential that can be exploited to advance and upgrade the sector. Hence the mountain region has made a mecca for visitors according to the unique characteristics of each region. Planning is a frequently used term both in tourism and elsewhere. And "has become a feature of the times" (Abboudi, 2013) In this study, we dealt with a topic that aims to identify and limit the most important indicators of mountain tourism in the Jabal Mesaad region using the Delphi technique. This technique was applied through two gradual phases, where the first phase included an open questionnaire question aimed at testing the pulse of experts in determining the indicators they deem appropriate for the development of tourism in mountain areas within the framework of sustainable tourism. After analyzing the various responses received in the questionnaires, we obtained (52) indicators according to the economic, social and psychological dimensions of tourism. (39) indicators that comply with the conditions required in the second phase were selected and accepted, including (19) indicators of the environmental dimension dominating the rest of the indicators, followed directly by the indicators of the economic dimension with (10) indicators, then the indicators of the social dimension with (10) indicators. According to the criteria adopted by the World Tourism Organization, we note that all indicators, both quantitative and qualitative, have the characteristics of à good index.